(untitled) (Education in the 21st Century, 2023)
Within the framework of this study, we referred to the parish, diocesan, and monastic charters of Eastern Armenian schools approved during the reign of All Armenian Catholicos Gevorg D. We drew parallels between the Eastern Armenian school and Russian state and spiritual schools. We have analyzed the content of the education of the examined period on the example of Yerevan diocesan school. We have paid special attention to the objectives of religious subjects in general education. Based on published school charters and studies, we analyzed the educational content of Eastern Armenian parochial, diocesan, monastic schools, and discovered what religious subjects were included in those educational centers. Until now, various researchers have reflected on the history of the Eastern Armenian school, the goals of education and upbringing, the activities of inspectors, textbooks, and teaching methods. It is interesting to find out what kind of religious courses were included in the schools of the examined period, in what order these subjects were studied, what goals they pursued. The coverage of these questions will help to form an idea about the order of study of such subjects in schools, to get acquainted with the goals of Christian education in the examined period. Thus, Russian state and religious schools had a four-tier system. Each school graduate was admitted to the next school level. The Eastern Armenian school was formed according to the logic of the Russian state and spiritual school systems. There were no state schools, but parish, diocesan, monastic schools were formed under the auspices of the Armenian Church. Parochial and diocesan schools provided secular education. Monastic schools were entered in order to obtain the title of clergyman. In the examined period, the Eastern Armenian educational policy was aimed at training secular specialists and clergy. Thus, We learn from the school charters that they were included ourses with the titles "Cathexis", "History of the Old and New Testament", "Church singing", "Theology". We learn about the order in which the above-mentioned subjects were studied from the school’s charters. An analysis of the subject headings provides evidence that the students received a comprehensive Christian education.